1989
DOI: 10.1002/ccd.1810170309
|View full text |Cite
|
Sign up to set email alerts
|

Large air embolus complicating coronary angioplasty

Abstract: With the substantial advances in technology and further refinements in the technique of coronary angioplasty, the potential for and manifestations of complications may have changed from those observed in populations studied previously. We describe a rare complication of percutaneous transluminal coronary angioplasty (PTCA), a large air embolus obstructing coronary flow, which is related to the newer technology. The air embolus was successfully extracted by aspiration through the balloon angioplasty catheter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…There are a few reports in the literature on the best active treatments for this entity, including hyperbaric oxygen therapy [5], forceful injection of saline to propel the air bubbles to the terminal portion of the coronary artery [2], and aspiration of the air from the coronary artery through the balloon angioplasty catheter [6]. We used the third technique, employing an over-the-wire balloon to aspirate the blood distal to the air bubble.…”
Section: Discussionmentioning
confidence: 98%
“…There are a few reports in the literature on the best active treatments for this entity, including hyperbaric oxygen therapy [5], forceful injection of saline to propel the air bubbles to the terminal portion of the coronary artery [2], and aspiration of the air from the coronary artery through the balloon angioplasty catheter [6]. We used the third technique, employing an over-the-wire balloon to aspirate the blood distal to the air bubble.…”
Section: Discussionmentioning
confidence: 98%
“…Case reports have described mechanical methods including aspiration of the bubbles ( sucking method ), 12 disruption or dislodgement by the guidewire, and forceful injection of saline ( pushing method ) to fragment the air embolus and allow dispersal distally. 13 , 14 Aspiration has been attempted with diagnostic or guide catheters and export aspiration catheters. 15 Another case showed that intracoronary thrombus aspiration catheter systems can be used safely and harmlessly to resolve air embolism.…”
Section: Discussionmentioning
confidence: 99%
“…Improvement of coronary slow flow can be accomplished by the treatment of vasospasm with intracoronary adenosine, nitroprusside, and calcium channel blockers such as nicardipine. Finally, bubble aspiration with thrombectomy catheters (Export, Diver, and Pronto catheters) or over‐the‐wire balloon catheters has been described in the literature to successfully achieve direct bubble extraction [10, 11].…”
Section: Discussionmentioning
confidence: 99%